Examining the Correlation between Objective Injury Parameters, Personality Traits, and Adjustment Measures among Burn Victims - Weissman, Oren; Domniz, Noam; Petashnick, Yoel R.; Gilboa, Dalia; Raviv, Tal; Barzilai, Liran; Farber, Nimrod; Harats, Moti; Winkler, Eyal; Haik, Josef (Frontiers in Public Health, 2015)
Background: Burn victims experience immense physical and mental hardship during their process of rehabilitation and regaining functionality. We examined different objective burn related factors as well as psychological ones, in the form of personality traits, that may affect the rehabilitation process and its outcome. Objective: To assess the influence and correlation of specific personality traits and objective injury related parameters on the adjustment of burn victims post-injury. Methods: 62 male patients admitted to our burn unit due to burn injuries were compared with 36 healthy male individuals by use of questionnaires to assess each group's psychological adjustment parameters. Multivariate and hierarchical regression analysis was conducted to identify differences between the groups. Results: A significant negative correlation was found between the objective burn injury severity (e.g. TBSA and burn depth) and the adjustment of burn victims (p<0.05, p<0.001, table 3). Moreover, patients more severely injured tend to be more neurotic (p<0.001), and less extroverted and agreeable (p<0.01, table 4). Conclusions: Extroverted burn victims tend to adjust better to their post-injury life while the neurotic patients tend to have difficulties adjusting. This finding may suggest new tools for early identification of maladjustment-prone patients and therefore provide them with better psychological support in a more dedicated manner.